Mechanical Response of Surrounding Rock of Karst Tunnel under Stress-Damage-Seepage Coupling Effect. (13th August 2022) - Gang-jian, An; Zheng-zheng, Cao; Hong-fei, Duan; Guo-sheng, Li; Ao, Li
Abstract : In order to reveal the mechanical response of surrounding rock of karst tunnel under stress-damage-seepage coupling effect, a new damage constitutive mechanical model of surrounding rock of karst tunnel under stress-damage-seepage coupling effect is established, which is calculated by the COMSOL Multiphysics in this paper. When the mechanical parameters are assigned to microelements of rock mass by the Weibull distribution function, the larger the m value is, the more homogeneous the rock mass is. The variation trend of strain energy density with m is similar to equivalent stress, which increases firstly and then decreases. The number of damage points increases with the increase in loading step and decreases rapidly after reaching the peak value and then remains a small number in the later loading stage. With the increase in γ, the stress range expands to the rock mass above the vault and below the floor; the stress value increases significantly, and the surrounding rock of karst tunnel is closer to strength limit, leading to the damage of rock mass. With the increase in γ, the area of the damage area in the upper part of the vault becomes larger, and most of the rock mass below the bottom plate is damaged; the damage area is semicircular, which indicates that both places are damaged by shearing action, resulting in the developed fissures. Besides, there are the distribution characteristics of "high value on both sides with a peak value and low value in the middle position" in the permeability distribution, and high permeability is located at the arch foot, and the low permeability is located at the floor. The larger the value of γ, the larger the permeability. The research achievements provide an important theoretical basis for prediction and treatment for dynamical disaster of karst tunnel.